Modification of the Mechanical Properties of the Sheet Two-Phase High-Strength Titanium Alloy VT 23 Due to Impulse Introduction of Energy. (2017) - Chausov, Mykola; Maruschak, Pavlo; Pylypenko, Andriy; Prentkovskis, Olegas; Hutsaylyuk, Volodymyr
Abstract: This study shows the effect of the specific impact-oscillatory loading (dynamic non-equilibrium processes) on the variation of the mechanical properties of the sheet two-phase high-strength titanium alloy VT 23. The results of fractographic research are used for interpreting the results of mechanical tests.